An Analysis of the Debate between al-Ṭūsī and al-Kātibī on Contingency Argument - Mehmet Tayfun Küçük (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
This article addresses a written debate between Najm al-Dīn al-Kātibī (d. 675 AH/1277 AD) and Nasīr al-Dīn al-Ṭūsī (d. 672 AH/1274 AD) on the contingency argument, which is one of the most well-known proofs offered in history regarding the existence of God. According to thinkers before al-Kātibī, the contingency argument verifies the Necessary Being, and then it debunks the possibility of infinite regress. By “earlier thinkers,” al-Kātibī means especially Avicenna (d. 428 AH/1037 AD) and Fakhr al-Dīn al-Rāzī (d. 606/1210). According to al-Kātibī, the notion of the Necessary Being was proved through the contingency argument they put forward, but a careful examination of their arguments indicates that they presented no definitive proof refuting the notion of infinite regress. Therefore, according to al-Kātibī, what Avicenna and Fakhr al-Dīn al-Rāzī claimed to prove the impossibility of infinite regress through the contingency argument is not valid. As al-Ṭūsī responded to al-Kātibī’s objections, a debate consisting of three letters from each side emerged between them. At the end of the debate, al-Kātibī found al-Ṭūsī’s explanations reasonable, and he admitted that they were correct. However, the parties did not mention the agreed version of the argument at the end of the debate. For this reason, I added this agreed argument at the end of this study in accordance with the parties’ declarations. The purpose of the present study is to analyse this debate in its natural order and to eliminate technical ambiguities it involves, defending Avicenna’s, al-Rāzī’s, and al-Ṭūsī’s philosophical position in the contingency argument about proving the impossibility of infinite regress through the argument. On the other hand, this debate is an epitome of the classical debate tradition. It is also significant in the sense that it reveals one of the best examples of the interdisciplinary discussion between kalām and philosophical schools, and the application of classical logic to theoretical disciplines. As a result of our analyses of the debate, we have concluded that the objections brought by al-Kātibī against the contingency argument in parallel with the conclusion of the debate accepted by the parties, maintain the contingency argument. According to this conclusion, the contingency argument is a proof which invalidates infinite regress while proving the existence of the Necessary Being.